THE EFFECT OF WORK-LIFE BALANCE, BURNOUT, WORK STRESS, AND ORGANIZATIONAL CIVIC BEHAVIOR (OCB) ON THE PRODUCTIVITY OF POLICE OFFICERS IN THE BUKIT KIJANG POLICE SECTOR IN 2025 - Rabul Yamin; Abdul Manan; Habibuddin Nasution; Mira Yona; Magneta Hisyam; A Ashari; Rehan Illiyansyah; Martin Pangihutan Simangunsong; Ibnu Aziz Alamsyah (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2026)
This study aims to analyze the influence of work-life balance, burnout, work stress, and organizational civic behavior (OCB) on employee productivity. As the demands for performance improvement increase in various organizations increase, understanding the psychological and behavioral factors that shape productivity has become critical. This quantitative research involved 34 respondents who were selected through saturated sampling techniques. Data were collected using standard Likert scale questionnaires and analyzed using SPSS version 26 through a series of statistical procedures, including validity and reliability testing, classical assumption testing, and multiple linear regression analysis. The results show that work-life balance and OCB have a positive and significant influence on productivity, showing that employees who maintain a healthy work-life balance and show positive behavior voluntarily tend to contribute more effectively to organizational goals. In contrast, work fatigue and work stress show significant negative influences, suggesting that prolonged emotional fatigue and high stress levels weaken employees' ability to perform optimally. A determination coefficient (R²) of 0.821 indicates that 82.1% of the variation in employee productivity can be explained by the four independent variables examined in this study, while the remaining 17.9% is due to other external factors not included in the model. These findings highlight the importance of organizational strategies that promote workload balance, minimize stress, reduce burnout, and encourage organizational civic behavior (OCB) to improve overall employee productivity. The study also provides practical implications for human resource management in designing policies that support psychological well-being and positive organizational civic behaviors. Keywords: Work-Life Balance; Burnout; work stress; Organizational Citizenship Behavior (OCB); Productivity